Tobacco Advertisement Liking, Vulnerability Factors, and Tobacco Use Among Young Adults. Issue 3 (17th September 2018) - Lienemann, Brianna A; Rose, Shyanika W; Unger, Jennifer B; Meissner, Helen I; Byron, M Justin; Baezconde-Garbanati, Lourdes; Huang, Li-Ling; Cruz, Tess Boley
Abstract: Introduction: Young adulthood (aged 18–24) is a crucial period in the development of long-term tobacco use patterns. Tobacco advertising and promotion lead to the initiation and continuation of smoking among young adults. We examined whether vulnerability factors moderated the association between tobacco advertisement liking and tobacco use in the United States. Methods: Analyses were conducted among 9109 US young adults in the nationally representative Population Assessment of Tobacco and Health (PATH) Study wave 1 (2013–14). Participants viewed 20 randomly selected sets of tobacco advertisements (five each for cigarettes, e-cigarettes, cigars, and smokeless tobacco) and indicated whether they liked each ad. The outcome variables were past 30-day cigarette, e-cigarette, cigar, and smokeless tobacco use. Covariates included tobacco advertisement liking, age, sex, race or ethnicity, sexual orientation, education, poverty level, military service, and internalizing and externalizing mental health symptoms. Results: Liking tobacco advertisements was associated with tobacco use, and this association was particularly strong among those with lower educational attainment (cigarettes, cigars) and living below the poverty level (e-cigarettes, smokeless tobacco). Conclusions: The association between tobacco advertisement liking and tobacco use was stronger among young adults with lower educational attainment and those living below the poverty level. Policies that restrict advertising exposure and promote counter-marketing messages in this population could reduce their risk. Implications: This study shows that liking tobacco advertisements is associated with current tobacco use among young adults, with stronger associations for vulnerable young adults (ie, lower education levels and living below the poverty level). Findings suggest a need for counter-marketing messages, policies that restrict advertising exposure, and educational interventions such as health and media literacy interventions to address the negative influences of tobacco advertisements, especially among young adults with a high school education or less and those living below the poverty level.